2006
DOI: 10.1007/bf03161174
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of flumazenil to antagonize gamma-hydroxybutyrate intoxication in a murine model

Abstract: In this model, pre-dosing flumazenil prior to GHB administration delayed clinical intoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Many substances such as (naloxone, flumazemil, or GABA B antagonists have been tried as potential antidotes, but there is no sufficient scientific evidence to support their routine application ( 51 , 52 , 53 , 54 , 55 ).…”
Section: Acute Poisoning With Ghbmentioning
confidence: 99%
“…Many substances such as (naloxone, flumazemil, or GABA B antagonists have been tried as potential antidotes, but there is no sufficient scientific evidence to support their routine application ( 51 , 52 , 53 , 54 , 55 ).…”
Section: Acute Poisoning With Ghbmentioning
confidence: 99%
“…In one study, physostigmine showed some promise in reversing GHB-induced altered states of consciousness [ 165 , 166 ], although its efficacy was later challenged [ 167 ]. Neither naloxone, a pure opiate antagonist [ 168 ], nor the selective benzodiazepine receptor antagonist flumazenil [ 169 ] were effective in reversing GHB sedation. A novel GABA-B antagonist was tested in mice as a way of lowering mortality caused by massive doses of GHB, but it did not seem to have any beneficial effects [ 170 ].…”
Section: Treatment Of Ghb Intoxicationmentioning
confidence: 99%
“…Representatively, physostigmine has shown the possibility of recovering the GHB-induced change in consciousness state [ 24 , 25 ]. However, physostigmine increases cardiovascular-related side effects [ 26 ], while naloxone [ 27 ], an opiate antagonist, and flumazenil [ 28 ], a selective benzodiazepine receptor antagonist, have not been found to be effective in reversing the sedative effects of GHB. Upon studying whether the γ-aminobutyric acid (GABA)-B receptor antagonist has an effect on reducing mortality due to excessive GHB intake in mice, no significant effect was found [ 29 ].…”
Section: Introductionmentioning
confidence: 99%